Constrains for seeking post-abortion care among adolescents and young women in Guangzhou, China: a cross-sectional study - Yiding Wang; Jinzhi Liu; Ribo Xiong; Yan Liu (BMC, 2021)
Abstract Background In China, post-abortion care (PAC) services mainly focus on married couples, such that adolescents and unmarried young womenhave limited access to those services for contraception counseling. The provision of youth-friendly PAC services in public hospitals is a new concept in China. This study examined the magnitude of PAC services utilization as well as factors influencing it's uptake among adolescents and young women in Guangzhou, China. Methods A cross-sectional study was performed from 1st March 2020 to 30th September 2020 using anonymous self-administered questionnaire among 688 women aged 15-24 years in Tianhe district, Guangzhou. The Multivariate logistic regression was used to determine factors that were significantly associated with the uptake of PAC services. Results The magnitude of PAC services utilization was 35.9% among adolescents and young women in Guangzhou, China. Students were 69.0% significantly less likely to use PAC services compared to women who had no job. Immigrants were 59.0% significantly less likely to use PAC services than their native counterparts. Women who had a feeling of stigma were 70.0% significantly less likely to use PAC services compared to those who did not feel stigmatized. Conclusions The study highlights the need to strengthen youth-friendly PAC services provision, and emphasizes the importance of education about both family planning and abortion services among disadvantaged sub-groups of women in the study setting.